COMBATING MRSA: AN EMPIRICAL STUDY – EVIDENCE FROM PAKISTAN - Rhasid, Anas; Qureshi, Usamah Rashid; Rashid, Aiman (Innovare Journal of Life Sciences, 2015)
Clinical microbiologist are facing challenge to defeat the bacterial infections like Methicillin Resistant Staphylococcus aureus (MRSA) in humans; due to unique resistance in bacterial strain. There are limited medication options left to conquer this deadly toxicities, if holistic approach is ignored. Also the linked complications and consequences of infections may increase beyond threshold levels; if exercise only a single array of drug therapy. This research article is based on primary microbial data collection (from sputum, urine and blood) in hospital; where the experiment focuses to investigate the highest risk vulnerable area. The preventive and curative measures are discussed along with alternative multiple array of medication with prudent selection to achieve targeted and optimum outcome.